The disaster-resilient smart city in Malaysia: The use of technology in flood management - Mohd Rozaimy, Ridzuan; Jamal Rizal, Razali; Ju, Soon Yew; Noor Amira Syazwani, Abd Rahman; Kong, Lai Kuan (Human Resource Management Academic Research Society (HRMARS), 2022)
Growth in metropolitan areas is occurring at a rate never seen before in human history. Almost two-thirds of the world's population is expected to reside in cities by the year 2050, up from a current percentage of more than half. Floods provide new risks and uncertainties at a time when growing urbanization is already putting a strain on finite resources and infrastructure. With the rise of smart cities as a solution to urban problems like flooding, many nations have made their largest cities more advanced than before. This study has accomplished its goal of generating interest in smart cities as a research topic by examining the use of smart city applications on flood management in Malaysia. It is hoped that this research would help policymakers develop a meaningful public policy and program to enhance smart city technologies, particularly for flood management. Keywords: Climate Change, Smart City, Flood, Flood Management, Information and Communication Technologies (ICT).